2018
DOI: 10.28991/cej-03091107
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Dry Resin on Moisture Sensitivity of Asphaltic Mixtures

Abstract: Moisture damage in asphaltic mixtures is defined by the loss of durability and resistance caused by the effect of moisture. The most common way to improve moisture damage in asphaltic mixtures is to use anti-strip additives. This study tended to use dry resin polymer additive to make a moisture-resistant asphaltic mixture. Two types of aggregate indicating different sensitivities against moisture were studied. In order to compare the effect of this material with other anti-strip additives, this study evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Furthermore, the addition of nanoclay resulted in a change on the structure; hence, the network appeared denser, which was attributed to aggregation of the nanoparticles. 19 These findings were in good agreement with the results obtained from mercury porosimetry analysis.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, the addition of nanoclay resulted in a change on the structure; hence, the network appeared denser, which was attributed to aggregation of the nanoparticles. 19 These findings were in good agreement with the results obtained from mercury porosimetry analysis.…”
Section: Resultssupporting
confidence: 86%
“…Shihab et al (2018) discovered that applying initial duration time with different temperatures highly affect the mechanical properties of soft clay soilfly ash based (Geopolymers. Jajin and Hamedi 2018) found that adding dry resin polymer increases adhesion and bonding in the mixture.…”
Section: Introductionmentioning
confidence: 99%